The Effect Cash and Inventory Turnover Return On Assets PT Industri Jamu dan Farmasi Sido Muncul Tbk - Annisa Zahra Amalina (Indonesian Financial Review, 2021)
This study aims to determine the effect of cash turnover and inventory turnover partially and simultaneously on Return on Assets at PT Industri Jamu dan Farmasi Sido Muncul Tbk. The data used in this study is in the form of the company's financial statements of PT Industri Jamu and Pharmacy Sido Muncul Tbk from 2013 to 2020. The analytical method used is a descriptive test, classical assumption test, simple and multiple linear regression, hypothesis testing, and the coefficient of determination and correlation. Based on the results of the study, it shows that cash turnover and inventory turnover partially and simultaneously have a significant effect on Return on Assets. The results of the determination coefficient test of 78.5% indicate that cash turnover and inventory turnover together contribute to Return on Assets, while 21.5% is influenced by other variables not examined by this study.